Factors associated with overweight/obesity in a cohort of people living with HIV over 50 years of age. Issue 4 (3rd April 2022) - Mazzitelli, Maria; Isabel Pereira, Branca; Moyle, Graeme; Asboe, David; Pozniak, Anton; Boffito, Marta; Milinkovic, Ana
ABSTRACT: Changes in body weight in people living with HIV vary by regimen components, timing of therapy introduction (naive, switch) and demographic factors. Our objective was to evaluate weight change and factors associated in an ageing cohort of treated subjects with HIV at Chelsea and Westminster Hospital. We found that the prevalence of obesity was similar to general population and was associated with a number of health conditions, which increase metabolic risk.